Jakarta Portaraits Of A Capital 1950 1980 - Scott Merrillees (Equinox Publishing, 2015)
Jakarta Portraits of a Capital 1950-1980 surveys the evolution of Jakarta during the first three decades after Indonesian independence had been achieved in 1949. Within its pages you are able to see what the capital looked like in the fairly recent past and understand how its development shaped what it has become today. The book only explores the growth of Jakarta’s physical landscape between 1950 and 1980 when the city became the capital of Indonesia after national sovereignty had finally been recognized by the Netherlands.